2003
DOI: 10.1021/ac0204707
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Potentiometric Determination of Peracetic Acid and Hydrogen Peroxide

Abstract: A rapid and highly selective potentiometric method for the simultaneous analysis of peracetic acid (PAA) and hydrogen peroxide (H2O2) has been proposed, for the first time, using glassy carbon (GC) as an indicator electrode and I2/I- potential buffer. On the basis of the large difference in the reaction rates of PAA and H2O2 with I-, which was confirmed using stopped-flow spectrophotometry, a transient potential response corresponding to the reactions of the two species with I- was observed. The response times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…0.076 mg/L) is based on the potential change in an iodide/iodine solution, in which peracid and H 2 O 2 react with iodide [72]. Since the response times for PAA and H 2 O 2 are a few seconds and several minutes, respectively, they can both be determined [73].…”
Section: Applied and Residual Peracid Concentrationsmentioning
confidence: 99%
“…0.076 mg/L) is based on the potential change in an iodide/iodine solution, in which peracid and H 2 O 2 react with iodide [72]. Since the response times for PAA and H 2 O 2 are a few seconds and several minutes, respectively, they can both be determined [73].…”
Section: Applied and Residual Peracid Concentrationsmentioning
confidence: 99%
“…It has been found that high exposure and eye contact will cause severe health problems. For the above reasons, many studies were focusing on developing reliable and commercial methods to detect its aqueous concentration (Davies and Deary, 1988;Pinkernell et al, 1996;Ruttinger and Radschuweit, 2000;Awad, et al, 2003), and to monitor its airborne concentration on a regular basis in workplace environments (Effkemann et al, 1999;Hecht et al, 2004;Henneken et al, 2006). However, field measurements of PAA are extremely sparse (Fels and Junkermann, 1993;Walker et al, 2006), and hence, the limited data restrain better understanding the role of PAA on atmospheric chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, an amperometric approach for the electroanalysis of PAA and H 2 O 2 was proposed [17 -19] which encountered however some operational troubles, such as time consumption, quite low sensitivity and the involvement of several steps. Furthermore, a potentiometric method was suggested [20] which is based on the different reaction rate of PAA and H 2 O 2 with iodide ions. In spite of its higher selectivity and sensitivity, this method suffers from the fact that its response is largely dependent on the solution pH, the concentrations of I 3 À and I À and the possible presence of catalysts.…”
Section: Introductionmentioning
confidence: 99%